Optimization technique based on cluster head selection algorithm for 5G-enabled IoMT smart healthcare framework for industry - Jaaz Z.A.; Ansari M.D.; Josephng P.S.; Gheni H.M. (De Gruyter Open Ltd, 2023)
5G mobile communication systems; Cluster analysis; Energy efficiency; Health care; Low power electronics; Medical applications; Network architecture; 'current; Cluster-head selections; Healthcare infrastructure; Internet of medical thing; Lower energies; Medical Devices; Optimization techniques; Selection algorithm; Wireless communications networks; WOWF-CHSA; Energy utilization